The Effect of the JISDOR Exchange Rate, Inflation, and Interest Rates on the Composite Stock Price Index (IHSG) for the 2020-2024 Period - Januadi, I Wayan; Suriani, Ni Nyoman; Idawati, Ida Ayu Agung (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the effect of the JISDOR exchange rate, inflation, and interest rates on the Jakarta Composite Index (JCI) on the Indonesia Stock Exchange for the 2020–2024 period. The research method used is a quantitative approach with multiple linear regression analysis. The data used is monthly secondary data obtained from Bank Indonesia, the Indonesia Stock Exchange, and other official sources. The independent variables in this study consist of the JISDOR exchange rate, inflation, and interest rates, while the dependent variable is the JCI. Data analysis techniques include classical assumption tests, multiple linear regression, simultaneous tests (F tests), and partial tests (t tests). The results show that simultaneously, the JISDOR exchange rate, inflation, and interest rates have a significant effect on the Jakarta Composite Index (JCI) for the 2020–2024 period. Partially, the JISDOR exchange rate has a positive and significant effect on the JCI. Meanwhile, inflation and interest rates do not show a significant effect on the JCI, indicating that fluctuations in both have not directly affected the index's movements. The implications of this research are expected to inform investors' investment decisions and the government and monetary authorities' formulation of economic policies that maintain capital market stability.